Hypothetical tax-benefit reforms in Hungary: Shifting from tax relief to cash transfers for family support - Ana Agúndez García; Michael Christl (European Commission, Joint Research Centre (JRC), 2023)
This paper evaluates two hypothetical budget-neutral reforms that shift resources from family tax expenditures to family cash transfers. We evaluate these reforms using a structural labor supply model based on the microsimulation EUROMOD model and EU-SILC data. We find that both reforms have an inequality-decreasing impact. However, when looking at labor supply responses for different household types, we show that the reforms have a non-negligible impact, especially for females in couple households. Additionally, we show that females in the middle of the income distribution in particular will reduce labor supply in response to the reforms.
Keywords: J20; J08; H31; 330; family benefits; reform; labor supply; discrete choice; microsimulation; EUROMOD